1986
DOI: 10.3758/bf03200038
|View full text |Cite
|
Sign up to set email alerts
|

Variations in radial maze performance under different levels of food and water deprivation

Abstract: Four groups of rats were tested on an eight-arm radial maze under a free-choice procedure. The subjects were maintained at either 80% or 100% of their preexperimental free-feeding weights through restricted access to either food or water. Water-deprived subjects received water in the maze; food-deprived subjects received food. Water-deprived subjects learned the task faster than food-deprived subjects. The four groups developed different response patterns. These were measured by the mean transition size, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
(30 reference statements)
1
12
1
Order By: Relevance
“…This tendency to avoid the final arm locations from a prior trial is further evidence against an end-of-trial "resetting" process in spatial working memory. Dale and Roberts (1986) replicated these effects when arms were baited with water as well as with food pellets. Roberts and Dale (1981) proposed that massing trials causes rats to become less certain about whether they last visited an arm during the current or previous trial.…”
mentioning
confidence: 58%
“…This tendency to avoid the final arm locations from a prior trial is further evidence against an end-of-trial "resetting" process in spatial working memory. Dale and Roberts (1986) replicated these effects when arms were baited with water as well as with food pellets. Roberts and Dale (1981) proposed that massing trials causes rats to become less certain about whether they last visited an arm during the current or previous trial.…”
mentioning
confidence: 58%
“…Second, and more importantly, the results from Experiment 2 indicated that such an effect seems to reflect confusion about which arm locations rats had been forced to visit most recently. Thus, intratrial PI in rats' spatial working memory in this study may be explained by the same temporal discrimination process that was considered to cause intertrial PI in rats' spatial working memory in the T-maze (Grant, 1981) or radial maze (Cohen et aI., 1994;Dale & Roberts, 1986;Roberts & Dale, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Grant (1981, Experiment 2), for example, found that decreasing the intertrial interval (ITI) between successive trials in the delayed alternation task from 60 or 30 sec to 0 sec generated steeper retention gradients in the second trial as the RI was increased from 0 to 40 sec. Rats also make more reentries during their final choices in the radial maze on later trials within a session even with ITIs as long as 240 sec (Dale & Roberts, 1986;Roberts & Dale, 1981). In these latter studies, rats tended to avoid the last four selected arm locations ofa previous trial during their first four initial choices on a current trial, another indication that memories from a preceding trial affect subsequent performance.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…This allows to facilitate the effectiveness of the visual cues. The mice had free access to water but were deprived food 12 h before the initial trial in order to increase their motivation for the task (Dale and Roberts, 1986). The start of each trial began with the mouse placed in the central platform facing the same arm.…”
Section: Radial Arm Maze Test (Ram)mentioning
confidence: 99%